Contribution of Plantation Forest on Wild Bees (Hymenoptera: Apoidea) Pollinators Conservation in Mount Slamet, Central Java, Indonesia - Widhiono, Imam; Sudiana, Eming; Yani, Edy (Biosaintifika: Journal of Biology & Biology Education, 2017)
Wild bee pollinators (Hymenoptera : Apiade) diversity and abundance were studied in three types of plantation forest on Mt. Slamet (Central Java Province, Indonesia). The aims of the research was to know the diversity and abundance of wild bee pollinators and to determine the possibility of plantation forest contribution on wild bees conservation. Sampling has been done at three stands: a pine forest (PF, with Pinus merkusii), an Agathis forest (AF, with Agathis damara) and a community forest (CF, with Albizia falctaria). Each habitat was divided into 5 line transect (100 x 5 m) and sweep nets were used to collect the wild bee samples. Sampling was done eah month from April to August 2015. The diversity of wild bees was high (12 species in 9 genera; members of the Apidae (7 species were dominant). The most abundant species across the forests were Apis cerana (343 individuals; 25.5% of total), Trigona laeviceps (195 individuals; 14.5%), and Megachille relativa (165 individuals; 12.3%). Measurements of species diversity (H), species evenness (E), habitat similarity (Ss) and species richness indicated that the wild bee species diversity in the region was relatively high (H = 1.275) to (H = 1.730);(E= 0.870) to (E = 0.93). The result showed that the diversity of wild bees in three different plantation forest habitats on Mt. Slamet were similar and can be concluded that plantation forest types were important for pollinator conservation, and an appropriate future preservation strategy should include of the areas of all plantation forest types.